Hierarchically Structured Bifunctional Electrocatalysts of Stacked Core–Shell CoS1−xPx Heterostructure Nanosheets for Overall Water Splitting. Issue 7 (6th April 2020) - Boppella, Ramireddy; Park, Jaemin; Lee, Hyungsoo; Jang, Gyumin; Moon, Jooho
Abstract: The rational design and strategy of obtaining stable bifunctional electrocatalysts with unique functionalities are prerequisite to achieving robust catalytic activity. In this study, a composition‐controlled partial sulfurization/phosphorization strategy to synthesize a doughnut‐like 3D heterostructured electrocatalyst for overall water splitting is proposed, wherein core–shell 2D CoS1− x P x nanosheets decorated with N‐doped carbon are self‐assembled to form a hierarchical 3D architecture. The composition and phase structure in core–shell CoS1− x P x can be readily modified by controlling the liquid phase sulfurization and subsequent phosphorization, thereby modifying the electronic structure and activating the intrinsic active sites. The resulting CoS1− x P x benefits from the unique structural features including high accessible active surface area, adequate amount of reactive sites, intimate interfacial coupling between the components, interconnected electron highway, and accelerated charge/mass transfer ability. Consequently, the optimized CoS0.46 P0.54 electrocatalyst achieves a catalytic current density of 10 mA cm −2 at overpotentials as low as 101 and 302 mV for hydrogen evolution reaction and oxygen evolution reaction, respectively, with outstanding long‐term operational stability in alkaline solution. The CoS0.46 P0.54 couple enables an alkaline water electrolysis with a current density of 10 mA cm −2 at a low cell voltage of 1.62 V, comparable to that of the RuO2 ||Pt/C couple (1.6 V). Abstract : Doughnut‐like 3D architectures composed of stacked core–shell 2D CoS1− x P x nanosheets are developed as high‐performance bifunctional electrocatalysts for the overall water splitting. A partial sulfurization/phosphorization strategy, which is used to tune the elemental and phase compositions, provides the intrinsic active sites and modulates the electronic structure to achieve excellent electrocatalytic hydrogen and oxygen evolution reactions.